Enhancer reprogramming: critical roles in cancer and promising therapeutic strategies - Jinshou Yang; Feihan Zhou; Xiyuan Luo; Yuan Fang; Xing Wang; Xiaohong Liu; Ruiling Xiao; Decheng Jiang; Yuemeng Tang; Gang Yang; Lei You; Yupei Zhao (Cell Death Discovery)
Abstract Transcriptional dysregulation is a hallmark of cancer initiation and progression, driven by genetic and epigenetic alterations. Enhancer reprogramming has emerged as a pivotal driver of carcinogenesis, with cancer cells often relying on aberrant transcriptional programs. The advent of high-throughput sequencing technologies has provided critical insights into enhancer reprogramming events and their role in malignancy. While targeting enhancers presents a promising therapeutic strategy, significant challenges remain. These include the off-target effects of enhancer-targeting technologies, the complexity and redundancy of enhancer networks, and the dynamic nature of enhancer reprogramming, which may contribute to therapeutic resistance. This review comprehensively encapsulates the structural attributes of enhancers, delineates the mechanisms underlying their dysregulation in malignant transformation, and evaluates the therapeutic opportunities and limitations associated with targeting enhancers in cancer.